2019
DOI: 10.1136/bmjpo-2019-000500
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy in children: a Cuban experience on leprosy control

Abstract: BackgroundChildren are believed to be the most vulnerable group to leprosy. Childhood leprosy reflects disease transmission in the community as well as the efficiency of ongoing disease control programmes. In Cuba, leprosy is not a national health problem; however, new childhood leprosy cases are diagnosed every year.ObjectiveWe summarise the experience of Cuba on childhood leprosy control over the past two decades.ResultsBetween 2000 and 2017, a total of 103 children in Cuba have been diagnosed with leprosy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
2
8
0
4
Order By: Relevance
“…Nevertheless, some studies report a higher proportion of multibacillary cases in the pediatric age similar to our study [39][40][41]. It is worth noting that these findings do not allow predicting trends; however, this indicate that children are in contact with cases of multibacillary leprosy in adults, which is the most frequent form of leprosy in adults in Cuba [17]. In this regard, Narang et al asserts that the risk can be up to 14 times higher when the contact is multibacillary, especially in lepromatous forms of the disease [42].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 49%
See 1 more Smart Citation
“…Nevertheless, some studies report a higher proportion of multibacillary cases in the pediatric age similar to our study [39][40][41]. It is worth noting that these findings do not allow predicting trends; however, this indicate that children are in contact with cases of multibacillary leprosy in adults, which is the most frequent form of leprosy in adults in Cuba [17]. In this regard, Narang et al asserts that the risk can be up to 14 times higher when the contact is multibacillary, especially in lepromatous forms of the disease [42].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 49%
“…Achievement of this noble goal requires reassessing surveillance and control actions in accordance to the goals of the WHO global leprosy strategy 2016-2020 to accelerate actions towards a world without leprosy [16]. Recently, we carried out a study about the Cuban experience in leprosy control activities from 2000 to 2017, in which socio-demographic and epidemiological variables were included along with serology and PCR testing to implement interventions for the early diagnosis of cases of leprosy during childhood [17]. Since childhood leprosy is an epidemiological indicator of persistent community transmission, we were interested in assessing all reported cases of leprosy in children in Cuba from 2012-2019, including new variables and considering a wider epidemiological approach.…”
Section: Introductionmentioning
confidence: 99%
“…No que diz respeito às características epidemiológicas na população pediátrica, em revisão sistemática realizada por Vieira et al (2018), foi constatado que o principal grupo acometido eram de meninos, entre 10 e 14 anos 11 . No Brasil, segundo o mais recente boletim epidemiológico de janeiro de 2020, os meninos de 0 a 14 anos, são acometidos em 52,3% dos casos 14 . Esses achados concordam com os encontrados nesta presente série de casos.…”
Section: Discussionunclassified
“…As crianças podem desenvolver qualquer forma clínica, como a chamada hanseníase nodular infantil, uma variação da forma tuberculóide que já foi descrita como sendo autolimitada 13 . Contudo, no Brasil, segundo o último Boletim Epidemiológico de Hanseníase de 2020, em relação a classificação operacional, atestou-se que 78,2% dos pacientes foram classificados como multibacilares, onde há a presença de 5 ou mais lesões, sendo preditivo de ocorrência de reações, complicações e sequelas no momento do diagnóstico 14 . Os casos aqui relatados representam variedades menos usuais para a faixa etária, com 4 casos da forma dimorfa e um caso da forma virchowiana, o que fala a favor de uma doença de longa data 15 , coincidindo com os números apresentados pela população adulta.…”
Section: Discussionunclassified
“…The only symptom of the disease is sometimes the thickening of the superficial nerves, especially the muscles of the auricular, superciliary and ulnar muscles. 19 Even though previous studies have stated the male dominance in childhood leprosy, a study by Sashidaranpillai et al found surprising female predominance in relapse cases. The higher susceptibility of teenage females to leprosy relapse can be due to hormonal changes and eventual alterations in the immune system with menarche.…”
Section: Leprosy In Children: Current Findingsmentioning
confidence: 95%